Micromechanical modeling of tension stiffening in FRP-strengthened concrete elements - Ghiassi, Bahman; Soltani, Masoud; Rahnamaye Sepehr, Sara (Sage, 2018)
This article presents a micromodeling computational framework for simulating the tensile response and tension-stiffening behavior of fiber reinforced polymer–strengthened reinforced concrete elements. The total response of strengthened elements is computed based on the local stress transfer mechanisms at the crack plane including concrete bridging stress, reinforcing bars stress, FRP stress, and the bond stresses at the bars-to-concrete and fiber reinforced polymer-to-concrete interfaces. The developed model provides the possibility of calculating the average response of fiber reinforced polymer, reinforcing bars, and concrete as well as the crack spacing and crack widths. The model, after validation with experimental results, is used for a systematic parameter study and development of micromechanics-based relations for calculating the crack spacing, fiber reinforced polymer critical ratio, debonding strength, and effective bond length. Constitutive models are also proposed for concrete tension stiffening and average response of steel reinforcing bars in fiber reinforced polymer–strengthened members as the main inputs of smeared crack modeling approaches.